2006
DOI: 10.1593/neo.05625
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection Alters Cellular Signal Cascades in Human Nasopharyngeal Epithelial Cells

Abstract: Epstein-Barr virus (EBV) latent infection is a critical event in nasopharyngeal carcinoma (NPC) tumorigenesis. EBV-encoded genes have been shown to be involved in immune evasion and in the regulation of various cellular signaling cascades. To elucidate the roles of EBV in NPC development, stable infection of EBV in nasopharyngeal epithelial cell lines was established. Similar to primary tumors of NPC, these infected cells exhibited a type II EBV latency expression pattern. In this study, multiple cellular sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(103 citation statements)
references
References 27 publications
4
99
0
Order By: Relevance
“…NP69 cells were established from primary nonmalignant nasopharyngeal epithelial cells and may represent a model of premalignant nasopharyngeal epithelial cells (34,54). The cell line was used to study Epstein-Barr virus interactions with the host cell (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…NP69 cells were established from primary nonmalignant nasopharyngeal epithelial cells and may represent a model of premalignant nasopharyngeal epithelial cells (34,54). The cell line was used to study Epstein-Barr virus interactions with the host cell (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that the response of NPC cells to EBV infection is mediated mainly by the NF-κB and STAT3 signal cascades [56]. EBV infection has been known to lead to NPC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled stable HK1 cell lines were maintained in neomycin and puromycin selection media and used for further analysis. EBV-infected HK1 (gift from George Tsao, Hong Kong University) and 293 (gift from Wolfgang Hammerschmidt, Helmholtz Center) cells were maintained in neomycin (800 g/ml) and hygromycin (100 g/ml) selection media, respectively (34,35). Infected cell lines were treated with 10 M MG132 for 8 h or 2 mM methyl-beta cyclodextrin overnight for LMP1 and LMP2A expression analyses.…”
Section: Methodsmentioning
confidence: 99%